Delineation of target volumes and organs at risk in adjuvant radiotherapy of early breast cancer: National guidelines and contouring atlas by the Danish Breast Cancer Cooperative Group. (May 2013) - Nielsen, Mette H.; Berg, Martin; Pedersen, Anders N.; Andersen, Karen; Glavicic, Vladimir; Jakobsen, Erik H.; Jensen, Ingelise; Josipovic, Mirjana; Lorenzen, Ebbe L.; Nielsen, Hanne M.; Stenbygaard, Lars; Thomsen, Mette S.; et al.
Abstract During the past decade planning of adjuvant radiotherapy (RT) of early breast cancer has changed from two-dimensional (2D) to 3D conformal techniques. In the planning computerised tomography (CT) scan both the targets for RT and the organs at risk (OARs) are visualised, enabling an increased focus on target dose coverage and homogeneity with only minimal dose to the OARs. To ensure uniform RT in the national prospective trials of the Danish Breast Cancer Cooperative Group (DBCG), a national consensus for the delineation of clinical target volumes (CTVs) and OARs was required. Material and methods. A CT scan of a breast cancer patient after surgical breast conservation and axillary lymph node (LN) dissection was used for delineation. During multiple dummy-runs seven experienced radiation oncologists contoured all CTVs and OARs of interest in adjuvant breast RT. Two meetings were held in the DBCG Radiotherapy Committee to discuss the contouring and to approve a final consensus. The Dice similarity coefficient (DSC) was used to evaluate the delineation agreement before and after the consensus. Results. The consensus delineations of CTVs and OARs are available online and a table is presented with a contouring description of the individual volumes. The consensus provides recommendations for target delineation in a standard patient both in case of breast conservation or mastectomy. Before the consensus, the average value of the DSC was modest for most volumes, but high for the breast CTV and the heart. After the consensus, the DSC increased for all volumes. Conclusion. The DBCG has provided the first national guidelines and a contouring atlas of CTVs and OARs definition for RT of early breast cancer. The DSC is a useful tool in quantifying the effect of the introduction of guidelines indicating improved inter-delineator agreement. This consensus will be used by the DBCG in our prospective trials.